Algebraic ship hull surfaces with a main frame from three plane curves in coordinate planes - Sergey N. Krivoshapko (RUDN Journal of Engineering Research, 2022)
One of the important problems of naval architects and designers is a choice of rational ship hull shape. A choice of ship hull form is based often on empirical formulae or on designers’ intuition. In the study, a method of determination of generalized explicit algebraic equations of theoretical ship hull configuration with three main cross sections given in advance and coinciding with waterline, main buttock (keel line), and midship section that are taken in the form of superellipses or in the form of any algebraic curve. Presented three of algebraic equations of surfaces with the same frame from three plane curves describes infinite number of ship hull surfaces. Having the same three plane curves one can get three algebraic surfaces of different order. The optimal shape, including cylindrical fragment or the ship hull shape containing two different - stern and bow - parts, joining along midship section, can be chosen with the help of methods of computer modelling with the application of artificial intellect using the materials of the paper. One can apply given results for the design of underwater apparatus on the early stage of the design.